2020
DOI: 10.3389/fphar.2019.01502
|View full text |Cite
|
Sign up to set email alerts
|

Intracellular ATP Delivery Causes Rapid Tissue Regeneration via Upregulation of Cytokines, Chemokines, and Stem Cells

Abstract: We have reported accelerated wound healing induced by intracellular ATP delivery in rabbits, through early massive accumulation, in situ proliferation, and M2 polarization of macrophages. Granulation tissue started to grow within first 24 h of treatment and continued the growth till the wound cavity is completely covered. However, the mechanisms underlying this macrophage response are totally unclear because no one has ever reported this before. In this study, we performed a preliminary exploration of the poss… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(23 citation statements)
references
References 40 publications
1
22
0
Order By: Relevance
“…Scale bar is 50 μm. function of the wound cells during the early ischemic stage (Sarojini et al, 2017;Mo et al, 2020). The healing events occurred in the current study also shows the same progression.…”
Section: Discussionsupporting
confidence: 78%
See 2 more Smart Citations
“…Scale bar is 50 μm. function of the wound cells during the early ischemic stage (Sarojini et al, 2017;Mo et al, 2020). The healing events occurred in the current study also shows the same progression.…”
Section: Discussionsupporting
confidence: 78%
“…Our excisional wound study revealed a unique phenomenon when ATP-vesicles were used: very early and massive macrophage accumulation, in situ proliferation, and M2 polarization ( Wang et al, 2009a ; Wang et al, 2010 ; Howard et al, 2014 ; Sarojini et al, 2017 ; Mo et al, 2020 ). The M2 polarized macrophages produce collagen directly to enhance healing at early time.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Moreover, innate immune cells such as neutrophils and macrophages continuously infiltrate during the inflammatory phase and interact with the high expression of chemokines, Macrophage inflammatory protein-2 (MIP-2) and Monocyte chemotactic protein-1 (MCP-1), up-regulate inflammatory mediators IL-1β, TNF-α, etc. result in continual amplification of signals of inflammatory until 13 days or more after injury (Wetzler et al, 2000;Tousoulis et al, 2013;Mo et al, 2019). Meanwhile, the continual differentiation and formation of proinflammatory macrophages can also stimulate the synthesis of Matrix metalloproteinases (MMPs) jointly with TNF-α, cause excessive destruction of extracellular Matrix and damaged granulation tissue formation (Acosta et al, 2008), inhibit proliferation and migration of fibroblasts and angiogenesis (Xu et al, 2013), activate innate immunity through ROS generated by oxidative stress (Warnatsch et al, 2015), activate NLRP3 inflammasome and lead to exacerbating wound inflammation (Lee et al, 2013;Mirza et al, 2014;Dai et al, 2017).…”
Section: Continuous Activation Of Innate Immunity Hidden Under Immune-aging and Inflamm-aging Hinders Diabetic Wound Healingmentioning
confidence: 99%
“…Under the pathological conditions of stress and inflammatory, caspase-1 released after the activation of NLRP3 inflammasome can also mediate a rapid programmed cell death pattern characterized by accompanying inflammatory response, called "Pyroptosis" (Wu et al, 2018). Pyroptosis induces the release of a large number of pro-inflammatory factors, eventually forming a cascade of amplified inflammatory responses (Jorgensen and Miao, 2015;Wang S. et al, 2019). In the state of DW, ROS and IL-1β can activate the NLRP3 inflammasome in Mp, promote the maturation and secretion of IL-1β, aggravate local inflammation through positive feedback, and hinder wound healing (Lee et al, 2013;Mirza et al, 2014;Dai et al, 2017).…”
Section: Overactivation Of Nlr Signaling Under Pathological Conditions Promotes Cascading Amplification Of the Inflammatory Response In Dmentioning
confidence: 99%